Afferent Baroreflex Dysfunction: Decreased or Excessive Signaling Results in Distinct Phenotypes - Norcliffe-Kaufmann, Lucy; Millar Vernetti, Patricio; Palma, Jose-Alberto; Balgobin, Bhumika J.; Kaufmann, Horacio (Seminars in Neurology, 2020)
Head and neck tumors can affect afferent baroreceptor neurons and either interrupt or intermittently increase their signaling, causing blood pressure to become erratic. When the afferent fibers of the baroreflex are injured by surgery or radiotherapy or fail to develop as in familial dysautonomia, their sensory information is no longer present to regulate arterial blood pressure, resulting in afferent baroreflex failure. When the baroreflex afferents are abnormally activated, such as by paragangliomas in the neck, presumably by direct compression, they trigger acute hypotension and bradycardia and frequently syncope, by a mechanism similar to the carotid sinus syndrome. We describe our observations in a large series of 23 patients with afferent baroreflex dysfunction and the cardiovascular autonomic features that arise when the sensory baroreceptor neurons are injured or compressed. The management of afferent baroreceptor dysfunction is limited, but pharmacological strategies can mitigate blood pressure swings, improve symptoms, and may reduce hypertensive organ damage. Although rare, the prevalence of afferent baroreflex dysfunction appears to be increasing in middle-aged men due to human papillomavirus related oropharyngeal cancer.
Keywords: afferent baroreflex; baroreflex failure; blood pressure; paraganglioma; neck cancer